2004
DOI: 10.1242/jcs.01082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microtubule sliding patterns inChlamydomonasflagellar axonemes reveals dynein activity on specific doublet microtubules

Abstract: Generating the complex waveforms characteristic of beating eukaryotic cilia and flagella requires spatial regulation of dynein-driven microtubule sliding. To generate bending, one prediction is that dynein arms alternate between active and inactive forms on specific subsets of doublet microtubules. Using an in vitro microtubule sliding assay combined with a structural approach, we determined that ATP induces sliding between specific subsets of doublet microtubules, apparently capturing one phase of the beat cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 56 publications
(90 reference statements)
5
54
0
Order By: Relevance
“…The output signal, presumably mediated by a radial spoke on one doublet microtubule, would be the activation of axonemal kinases located near I1-dynein Gaillard et al, 2006]. Consistent with these ideas, the central pair apparatus is asymmetric in structure and composition [Mitchell and Sale, 1999;Mitchell and Yokoyama, 2003;Mitchell, 2003a;Wargo and Smith, 2003;Smith and Yang, 2004;Lechtreck and Witman, 2007] and the position of the central pair correlates with sites of active sliding [Wargo and Smith, 2003;Wargo et al, 2004] and the position of doublets relative to the bend [Mitchell, 2003a;Smith and Yang, 2004]. The results have also revealed a functional role for kinases (PKA, CK1) and phosphatases (PP1, PP2A) that are physically localized in the axoneme Sale, 1996, 1997;King and Dutcher, 1997;Porter and Sale, 2000;Gaillard et al, 2001Gaillard et al, , 2006Gokhale et al, 2006].…”
Section: Functional Role Of I1 In Regulation Of Flagellar Bending: a mentioning
confidence: 87%
“…The output signal, presumably mediated by a radial spoke on one doublet microtubule, would be the activation of axonemal kinases located near I1-dynein Gaillard et al, 2006]. Consistent with these ideas, the central pair apparatus is asymmetric in structure and composition [Mitchell and Sale, 1999;Mitchell and Yokoyama, 2003;Mitchell, 2003a;Wargo and Smith, 2003;Smith and Yang, 2004;Lechtreck and Witman, 2007] and the position of the central pair correlates with sites of active sliding [Wargo and Smith, 2003;Wargo et al, 2004] and the position of doublets relative to the bend [Mitchell, 2003a;Smith and Yang, 2004]. The results have also revealed a functional role for kinases (PKA, CK1) and phosphatases (PP1, PP2A) that are physically localized in the axoneme Sale, 1996, 1997;King and Dutcher, 1997;Porter and Sale, 2000;Gaillard et al, 2001Gaillard et al, , 2006Gokhale et al, 2006].…”
Section: Functional Role Of I1 In Regulation Of Flagellar Bending: a mentioning
confidence: 87%
“…We have observed that lf1, lf2, and lf4 flagellar waveforms show serious deviations from the WT waveform. This points the way to further work involving an in vitro microtubule-sliding assay with isolated axonemes so as to examine the possible role of the central pair in modulating dynein activity on specific doublet microtubules [38][39][40]. A closer look at mutant cell shapes is, therefore, warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic analyses of C1-defective mutants (e.g., Dutcher et al, 1984;Mitchell and Sale, 1999) as well as recent structural and functional studies (Smith, 2002a;Smith, 2002b;Wargo and Smith, 2003;Wargo et al, 2004) have provided ample evidence to indicate that the C1 microtubule plays a role in regulation of motility. In addition, each C1 projection appears to make a unique contribution to modulation of flagellar motility.…”
Section: Discussionmentioning
confidence: 99%
“…This control mechanism is disrupted in certain mutants including the C1-defective mutant, pf6 (Wargo et al, 2004). Our functional studies of dynein-driven microtubule sliding in isolated axonemes indicate that calmodulin and a calmodulin-dependent kinase may mediate the calcium signal and that the central apparatus and radial spokes are key components of the calcium signaling pathway (Smith, 2002b).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation